Experimental synthesis of sound pressure fields for active structural acoustic control testing. (May 2014) - Algermissen, Stephan; Meyer, Sebastian; Appel, Christina; Monner, Hans P
For next generation aircraft, contra rotating open rotor propulsion systems are currently discussed. Their economic advantages are in conflict with their high noise emission, which concentrates in distinct frequency bands. To bring contra rotating open rotor engines into operation at commercial aircraft and to maintain the passenger comfort level, active systems for noise reduction are considered. In this article, a contra rotating open rotor noise simulator for the future testing of active systems is presented. The simulator consists of a 14 × 8 loudspeaker array, which is placed close to a test fuselage. Driving each loudspeaker by a particular signal, complex sound pressure fields can be synthesized on the fuselage. The algorithm presented here calculates loudspeaker signals to synthesize the target sound pressure spectra on the fuselage. These target spectra were derived from numerical contra rotating open rotor engine simulations, coupled with a Ffowcs Williams–Hawkings solver to propagate the calculated sound pressure field toward virtual surface microphone positions on the test fuselage. Requirement for such synthesis is the knowledge of the transfer paths from all loudspeakers to all surface microphones. In experiments, these paths are measured, and the loudspeaker signals are synthesized by the algorithm. Finally, measurements with the loudspeaker array and a microphone array are shown which prove the concept.